The progressive creation of the early mother-child bonding - Traverso Koroleff, Pierina (2001)
One of the research areas in mother-child health has focused on examining which are the signs inmothers' psychological functioning that would lead to a further disturbed development in an infant.The perspective of this paper has deviated from this research area. Natural observation of an infantduring his/her first year of life suggests that early mother-child affective bonding grows and strengthens progressively, even mother's behavior is not totally adequate. This article al so suggests that mother and child feed back each other in this early bonding.